Real-world registry-based study on apremilast use in psoriasis and psoriatic arthritis in Finland - Koskivirta I; Ruotsalainen J; Kurki S; Lakkakorpi P; Salminen-Mankonen H; Pirilä L; Harvima R; Palomäki A (Taylor & Francis, 2025)
Objectives
This study assessed the position of apremilast in the treatment pathway of psoriasis (PsO) and psoriatic arthritis (PsA) in Finnish clinical practice, compared the characteristics of apremilast and biologic therapy users, evaluated persistence with apremilast and identified factors influencing treatment discontinuation.
Method
This retrospective study used data from Finnish national health registries. The target group was identified based on L40* diagnosis and medication records between 2015 and 2018. Treatment persistence was analysed using Kaplan–Meier curves and Cox regression.
Results
Of eligible patients (PsO 31 202; PsA 12 386), 1% (n = 471) used apremilast and 10% (n = 4214) biologics, apremilast users being older (mean age 55.9 vs 52.4 years, p < 0.001) with a higher Charlson comorbidity score (0.71 vs 0.54, p < 0.001). Most patients switched to apremilast from conventional synthetic therapy (PsO 75%; PsA 76%); 47% of patients remained on apremilast during the observation period (PsO 58%; PsA 42%). Most patients discontinuing apremilast switched to biologics (PsO 51%; PsA 51%). Apremilast persistence increased with age (p = 0.042) and was higher in PsO than in PsA (median 14 vs 11 months; p = 0.005). Compared to prior conventional synthetic therapy, prior biologic therapy decreased persistence (hazard ratio for discontinuation 2.15, 95% confidence interval 1.42–3.25).
Conclusion
In Finnish clinical practice, apremilast is mainly used between conventional synthetic therapy and biologics, with at least as high treatment persistence as reported in previous studies. Apremilast users were older with higher comorbidity burden than biologics users.